The Significance of Meals on Wheels of Pitt County on the Well-being of Homebound Older Adults - Schulte, Jess (East Carolina University, 2022)
The purpose of the current study is to understand the significance of the Meals on Wheels (MOW) home-delivered meals program on the well-being and quality of life of older adults in Pitt County, North Carolina. Qualitative and quantitative data was collected from 50 MOW recipients through telephone surveys about how MOW contributes to their well-being. Three themes emerged from the analysis: clients’ needs and limitations, a desire to stay independent, and appreciation for MOW and its volunteers. Participants had a range of needs and limitations that involved health conditions, nutrition, low-income, lack of access to transportation, and isolation. Recipients also indicated the desire to stay independent and age in place rather than living in a nursing home or assisted living facility. Appreciation and gratitude was also expressed by participants toward the MOW program because of the convenient aid that the service provides in addition to the social interaction with volunteers. The findings of the study support that of previous research that claims MOW plays a vital role in the well-being of its recipients regarding nutrition, socialization, and aging in place. The recent knowledge from the study can help to inform service providers, raise awareness, and increase support for interventions that target food insecurity in the older population.
Keywords: Meals on Wheels, well-being